Migration Literacy: Global Preparedness and Awareness AmongProspective Indonesian Migrant Workers in Japan (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study aims to analyze migration literacy in shaping the readiness and global awareness of Indonesian prospective migrant workers (CPMI) prepared to work in Japan. The research problem arises from the limited preparedness of CPMI, which involves not only technical skills but also language, cultural, administrative literacy, and global awareness. This study employed a descriptive qualitative approach involving 20 CPMI undergoing training at several job training institutions (LPK) in the Semarang region. Data were collected through in-depth interviews, observations, and documentation, and analyzed thematically. The findings show that CPMI migration literacy is at a moderate level, with strengths in work ethics awareness and the use of information technology, but weaknesses remain in technical language comprehension, employment administration, and deeper cultural adaptation. Global awareness has begun to develop; however, it is still largely driven by economic motivation and not fully supported by adaptive readiness and critical literacy. The study concludes that migration literacy is a multidimensional competence essential for global work readiness. Therefore, a more integrative and practical training model is needed to enhance the readiness and protection of Indonesian migrant workers in Japan.
Keywords: migration literacy; Indonesian migrant workers; global awareness; Japan; LPK